The relationship between nutrition in infancy and cognitive performance during adolescence - Anett Nyaradi; Wendy H. Oddy; Siobhan Hickling; Jianghong Li; Jonathan K. Foster (Frontiers in Nutrition, 2015)
[Objectives:] In this study, we aimed to investigate the long-term associations between breastfeeding duration during infancy, diet quality as measured by a diet score at 1 year of age, and cognitive performance during adolescence. [Methods:] Participants (n = 717) were recruited from the West Australian Pregnancy Cohort (Raine) Study, a prospective longitudinal study of 2868 children and their families based in Perth, WA, Australia. Breastfeeding duration and an early diet score at age 1 year were used as the main predictor variables, while a computerized cognitive battery (CogState) was used to assess adolescents' cognitive performance at 17 years. The diet score, which has seven food group components, was based on a 24-h recall questionnaire completed by the mother at 1 year of age. A higher diet score represents a better, more nutritious eating pattern. Associations between breastfeeding duration, diet score, and cognitive performance were assessed in multivariable regression models [Results:] Higher diet scores at 1 year representing better diet quality were significantly associated with faster reaction times in cognitive performance at 17 years [Detection Task (DET): β = -0.004, 95% CI: -0.008; 0.000, p = 0.036; Identification Task (IDN): β = -0.004, 95% CI: -0.008; 0.000, p = 0.027]. Breastfeeding duration (≥4 months) was also significantly associated with a shorter reaction time, but only for males (DET: β = -0.026, 95% CI: -0.046; -0.006, p = 0.010). [Conclusion:] Nutrition in early childhood may have a long-term association with fundamental cognitive processing speed, which is likely to be related to enhanced brain development in the first year of life.
Keywords: 300; nutrition; breastfeeding; cognitive performance; CogState; early childhood; adolescence; Raine study